Pelaksanaan Prinsip Responsibility To Protect PBB Dalam Penanganan Krisis Kemanusiaan Di Afrika (Republik Afrika Tengah, Sudan & Nigeria) - Yuniarti; Frentika Wahyu Retnowatik; Etha Pasan (Journal Social Politica, 2021)
The changing nature of conflict post World War II from inter-state conflict to intra-state conflit resulted in insistent humanitarian crises. Based on UNOCHA Report 2010, in 2009, Africa had the biggest number of humanitarian crises. This article aiming at explaining the humanitarian crises in Africa, the effort to deal with the crises from humanitarian intervention and the rise of Responsibility to Protect (R2P) Principles, and implementation of principles in Central African Republic, Sudan and Nigeria. In general, UN Security Council is a central institution which the highest authority in world security issue to implement the R2P Principles. However, the principles enforcement in these three cases interposed African Union as a main actor to implement UN Security Council mandate as well as the International Criminal Court as a prosecutor and adjudicator crimes against humanity .